The Impact of Financing of the Agricultural Business by Sharia Bank and Work Motivation to Increase the Exchange Rate of Farmers in West Java Province - Sasmita, Muhammad Zeinny Hasbunallah; Saprudin, Nandu (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This quantitative study examines the impact of Islamic bank financing, social media marketing, and work motivation on farmers' exchange rates in West Java from 2017 to 2021. The farmer exchange rate, which measures purchasing power by comparing income to expenses, serves as the key welfare indicator (dependent variable). The research tests specific hypotheses using a conclusive design and a mixed-methods approach. Data collection combines secondary data on financing amounts from Islamic banks with primary data gathered via surveys and questionnaires. These instruments measure farmers' perceptions of social media advertising effectiveness and their levels of work motivation, ensuring representative and reliable inputs. The analysis employs a robust statistical procedure. After descriptive statistics, the data undergoes validity, reliability, and classical assumption testing. The core analysis uses multiple linear regression to measure the individual and combined influence of the three independent variables on changes in the exchange rate. The anticipated results are poised to contribute significantly to both theory and practice. Academically, the study integrates Islamic finance and digital marketing into agribusiness literature. Practically, it offers evidence-based insights. Islamic banks can optimize their agricultural financing and outreach, while local governments can formulate targeted policies to enhance sustainability and directly improve farmer prosperity in West Java.